Riding Waves of Change: A Review of Personas Research Landscape Based on the Three Waves of HCI - Chu, Hiang Goh; Narayanan, Kulathuramaiyer; Tariq, Zaman (Springer New York LLC, 2017)
With the current growth of personas studies in HCI, we undertook the mapping out of the research approaches done for the past 18 years to provide an overall view on the landscape of personas research. Based on the narrative literature review of published work and paired with the three waves of HCI research development, we identified (1) the publication milestones of personas, (2) established genre of research approaches, and (3) the emerging issues and research trends. By looking at historical development of personas, the studies highlighted some key areas which might be the future trends of personas in the new wave of HCI. These will provide significant insight and direction for future research of personas.